Spirituality for youth-work : new vocabulary, concepts and practices - Daughtry, Phil; Devenish, Stuart (Cambridge Scholars Publishing, 2016)
This book addresses a systemic gap in existing studies on human services and youth work. While the notion of spirituality does make rare appearances in such literature, it is often vaguely defined and underdeveloped both as a concept and as a mode of practice. This ambiguity is symptomatic of the broader shift in the sociological context of Western and global societies that has been referred to variously as post-modern, late-modern and post-secular. From the perspective of the relationship between human development and the spiritual/theological, we live in a "time between times". We have not y.